STUDENTS' ERROR ANALYSIS IN WRITING DESCRIPTIVE TEXT - 1Agnes Pebiani Br.Nadeak; Sheilla Nur Affifa; Minda Mora Br Barus (elt, 2020)
ABSTRACT This research aims to analyze and classify the errors made by students in writing descriptive text. This research used descriptive qualitative method. The participants were the X-1 grade Senior High School students of SMA Swasta Puteri Sion, in the academic year of 2020/2021. Data for this research were taken by doing a task. The researchers gave a paper about descriptive text which has no punctuations on it, then sudents answered it. This study showed that there were four errors that students made which are addition, misinformation, misordering and omission. The percentage error of addition was 23,5%, error of misinformation 21,3%, error of misordering 18,4% and error of omission 36,8%. According to the percentage, it could be concluded if error of omission is the most dominant error by students with 36,8% and error of misordering is the lowest error students made with 18,4%. Keywords : Punctuation Mark, Descriptive Text, Writing